Cardiovascular mortality among pulp mill workers. Issue 4 (April 1990) - Jäppinen, P; Tola, S
Abstract : A mortality study, concentrating on cardiovascular mortality, was undertaken among Finnish sulphite mill workers exposed to sulphur dioxide and sulphate mill workers exposed to hydrogen sulphide and organic sulphides. They had been employed continuously for at least one year between 1945 and 1961. National death rates were used for comparison and mortality was followed up until 31 December 1981. Among the cohort exposed to sulphur dioxide (2268 person-years), an excess of cardiovascular deaths was noticed among the men (24 obs, 19.4 exp, SMR 123) due to an excess of coronary deaths (18 obs, 12.4 exp, SMR 145). The cardiovascular mortality was not affected by the duration of occupational exposure or follow up period in this cohort. Among the men exposed to hydrogen sulphide and organic sulphides (4179 person-years), there was also an excess of cardiovascular deaths (37 obs, 24.7 exp, SMR 150) due to an excess of coronary deaths (25 obs, 16.7 exp, SMR 150). These excesses increased with longer follow up period. As common risk factors of coronary heart disease could not explain the findings in the sulphate mill cohort, they may be associated with exposure to hydrogen sulphide and organic sulphides.